1983
DOI: 10.1152/ajpregu.1983.245.3.r311
|View full text |Cite
|
Sign up to set email alerts
|

Upper thoracic sympathetic neuron responses to input from urinary bladder afferents

Abstract: The aim of the present study was to evaluate the organization of neural circuitry responsible for the intersegmental transmission of input from urinary bladder afferents to sympathetic preganglionic neurons (SPNs). The electrical activity of SPNs was recorded from axons of the cervical sympathetic trunk in anesthetized central nervous system (CNS)-intact and in unanesthetized midcollicular-decerebrate or acute C1 spinal cats. In all three preparations, tonically active SPNs were excited or inhibited by 1) elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In our opinion, motoneurone inhibition secondary to bladder distension represents a viscero-somatic reflex activated by nociceptive afferent input and mediated by the propriospinal system. A propriospinal system-mediated reflex accords with previous studies suggesting that in cats, the propriospinal system is involved in the intersegmental transmission of input from bladder afferents to upper thoracic sympathetic pre-ganglionic neurones (Schondorf et al, 1983;Weaver, 1985). In addition, the activation of the DNIC by painful somatic stimuli leaves the H-reflex unchanged (Willer et al, 1989).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our opinion, motoneurone inhibition secondary to bladder distension represents a viscero-somatic reflex activated by nociceptive afferent input and mediated by the propriospinal system. A propriospinal system-mediated reflex accords with previous studies suggesting that in cats, the propriospinal system is involved in the intersegmental transmission of input from bladder afferents to upper thoracic sympathetic pre-ganglionic neurones (Schondorf et al, 1983;Weaver, 1985). In addition, the activation of the DNIC by painful somatic stimuli leaves the H-reflex unchanged (Willer et al, 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Because the H-reflex depression coincided with maximum filling, when subjects felt pain and could no longer delay micturition, the responsible vesical afferent fibres presumably conveyed a nociceptive input classically relayed by unmyelinated and thinly myelinated fibres. In humans, the visceral nociceptive inputs appear to act on at least two systems, the diffuse noxious inhibitory controls (DNIC) (Cadden and Morrison, 1991) and the propriospinal system (Schondorf et al, 1983;Weaver, 1985). The DNICs, postulated in animals and humans (Le Bars et al, 1979aBars et al, ,b, 1981Villanueva et al, 1986a,b;Cadden and Morrison, 1991;De Broucker et al, 1990;Bouhassira et al, 1993), are mediated by a loop involving supraspinal structures and modulate the activity of spinal cord neurones that receive widespread noxious visceral and somatic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the modulation of the H-re¯ex amplitude in normal subjects during bladder ®lling is mediated by the propriospinal system (Inghilleri et al [17]). This concept is supported by studies in cats that suggest that the propriospinal system is involved in the intersegmental transmission of input from bladder afferents to upper thoracic sympathetic pre-ganglionic neurones [18,19].…”
Section: Discussionmentioning
confidence: 83%
“…Previous reports showed that cardiovascular sympathetic activity in the bladder filling phase disappeared in the voiding phase, and that blood pressure and heart rate returned to baseline after voiding in normal subjects. [15][16][17][18][19][20][21][22][23][24][25] Furthermore, in the voiding phase of experimental animals, the bladder parasympathetic nerve supply is excited, while the urethral sympathetic nerve supply is inhibited. These changes return to normal immediately after voiding.…”
Section: During and After Voidingmentioning
confidence: 99%